“The New Generation”: Cooperative Education at the Day School on Dalles 38C Indian Reserve, 1890-1910 - Luby, Brittany; Labelle, Kathryn (Ontario History)

(untitled) (The Ontario Historical Society, 2015)
Modern research into Aboriginal education focuses on the de-culturation, physical, and emotional abuse that Indigenous students experienced at school. This focus results, in part, from an emphasis on sources written by settlers, which detail little of the lived experience of Indigenous students. Using a series of interviews conducted in Kenora, Ontario, with the Anishinabek woman Matilda (Ogimaamaashiik) Martin of Dalles 38C Indian Reserve, this paper examines that lived experience and concludes that Aboriginal education was more collaborative than has been described, particularly before the enforcement of aggressive civilization. This collaboration, however, occurred in the context of ongoing colonial incursions in to Aboriginal land and life, which gradually edged out Aboriginal forms of education.